ANALYSIS OF WEB-BASED ONLINE SERVICES FOR GPS RELATIVE AND PRECISE POINT POSITIONING TECHNIQUES - Ocalan, Taylan; Erdogan, Bahattin; Tunalioglu, Nursu (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2013)
Nowadays, Global Positioning System (GPS) has been used effectively in several engineering applications for the survey purposes by multiple disciplines. Web-based online services developed by several organizations; which are user friendly, unlimited and most of them are free; have become a significant alternative against the high-cost scientific and commercial software on achievement of post processing and analyzing the GPS data. When centimeter (cm) or decimeter (dm) level accuracies are desired, that can be obtained easily regarding different quality engineering applications through these services. In this paper, a test study was conducted at ISKI-CORS network; Istanbul-Turkey in order to figure out the accuracy analysis of the most used web based online services around the world (namely OPUS, AUSPOS, SCOUT, CSRS-PPP, GAPS, APPS, magicGNSS). These services use relative and precise point positioning (PPP) solution approaches. In this test study, the coordinates of eight stations were estimated by using of both online services and Bernese 5.0 scientific GPS processing software from 24-hour GPS data set and then the coordinate differences between the online services and Bernese processing software were computed. From the evaluations, it was seen that the results for each individual differences were less than 10 mm regarding relative online service, and less than 20 mm regarding precise point positioning service. The accuracy analysis was gathered from these coordinate differences and standard deviations of the obtained coordinates from different techniques and then online services were compared to each other. The results show that the position accuracies obtained by associated online services provide high accurate solutions that may be used in many engineering applications and geodetic analysis.
Keywords: GPS; Precise Point Positioning (PPP); Post-Processing; Relative Positioning; Web-Based Online Services; Geochemistry & Geophysics; Remote Sensing